Analysis of the effectiveness of using Kahoot! in university degrees in building engineering - David Bienvenido-Huertas; Carlos Rubio-Bellido; Miguel León-Muñoz (OmniaScience, 2023)
Gamification is increasingly used for better content assimilation. However, it is hardly used in theoretical and technical courses related to building and architecture. This study focuses on assessing the use of gamification with Kahoot! to arouse students' interest and to ease content assimilation. Experimentation was undertaken during the 2020/2021 and 2021/2022 academic years. All students enrolled in the course participated in experimentation: 67 and 65 students, respectively. Gamification sessions took place in the middle and at the end of each academic year (the week before partial exams). Students were also surveyed to assess their degree of satisfaction with gamification sessions. The results showed that gamification dynamics improved students' performance in exams, obtaining a lower percentage of failures and increasing higher marks. Cluster analysis results also showed that students' performance in Kahoot! is not a clear indicative of their performance in exams, so it is useful as a self-assessment tool. Moreover, most students positively assessed gamification sessions for better content assimilation. This study stresses the implementation potential of Kahoot! in teaching dynamics in university degrees in architecture and building engineering.